HUBUNGAN PERAN ORANG TUA DENGAN STATUS KARIES GIGI PADA MURID SDN 1 JEUMPET KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Elfi Zahara; Warzaton Nisa (Jurnal Mutiara Kesehatan Masyarakat, 2022)
Parents, especially mothers, play an important role in maintaining dental health to see the development and growth of children's teeth. Currently, tooth decay in children is considered a natural thing, so parents think that they do not need to deal with it. From the initial data from interviews with parents of students, parents still lack a role in maintaining the health of children's teeth and mouth. And the results of the dental caries examination of 9 students who were examined on average had dental caries with a category of 5.2 (high).The purpose of this study was to determine the relationship between the role of parents and dental caries status in students at SDN 1 Jeumpet, Kec. Darul Imarah, Aceh Besar District. This type of research is analytic with cross sectional study method and uses a questionnaire as an instrument. The sampling technique in this study was using a saturated sampling technique, because all the population was sampled, amounting to 35 students and 35 parents of students at SDN 1 Jeumpet.The results showed that the role of parents in the good category had the most dental caries status in the low category as many as 3 students (60.0%), the role of parents in the moderate category had the most dental caries status in the moderate category as many as 9 students (64.3% ) and the role of parents in the less category having the highest dental caries status in the high category was 7 students (43.8%). The results of the statistical test obtained P < 0.001 from the value of = 0.05 because P = 0.001 < = 0.05.Based on the results, it can be concluded that there is a relationship between the role of parents and the status of dental caries. Based on the conclusion, it is suggested that parents can increase their roles as educators, motivators, facilitators in maintaining children's oral and dental health.